Long-term influence of associating an antibacterial agent with GIC on bond strength to caries-affected dentin - Ana Carolina de Oliveira Becci; Luana Mafra Marti; Angela Cristina Cilense Zuanon; Fernanda Lourenção Brighenti; Elisa Maria Aparecida Giro (Universidade Estadual de Campinas, 2017)
Aim: To evaluate the bond strength of a GIC associated with chlorhexidine (CHX) to sound and caries-affected dentin, immediately and after six months of storage. Methods: Sixty molars were assigned to two groups of 30 teeth. One had flat dentin surfaces produced and submitted to caries induction to obtain a caries-affected dentin.  In the other group dentin was maintained sound. Teeth of each group were randomly reassigned to three subgroups (n=10) according to the concentration of CHX added to the GIC (0%, 1% and 2% by weight).  Two specimens (1mm diameter x 1 mm high) of the same material were constructed on each dentin surface. One was submitted to the microshear bond strength (µSBS) test after 24 hours and the other after 6 months of storage in water at 37oC. Failure modes were analyzed under a stereomicroscope. Bond strength data were analyzed by three-way ANOVA followed by Games-Howell tests for multiple comparisons, and failure modes by the Chi-square test (α = 0.05). Results: The µSBS values obtained to sound dentin were higher compared with those to caries-affected dentin (p≤0.001). In sound dentin, the group with 2% CHX showed lower  µSBS values compared with 0% and 1% CHX after 24 hours (p=0.005 and p=0.032 respectively). In caries-affected dentin, after 24 hours, µSBS in group with 1% CHX was statistically higher than the values in groups with 2% CHX after 24 hours (p=0.001) and 1% CHX after 6 months (p=0.024). Irrespective of the condition of substrate, comparisons showed no statistically significant differences between the other groups (p≥0.053). Cohesive in material and mixed failures prevailed for all groups. Conclusions: The addition of CHX at concentrations of up to 2% to the GIC did not affect the bond strength of the material to sound and caries-affected dentin in a long-term evaluation.